ЖАС СПОРТШЫНЫҢ ӨЗИН-ӨЗИ ҚАДАҒАЛАЎ КҮНДЕЛИГИ ӨЗГЕШЕЛИКЛЕРИ - Мырзамбетов, П.Ш.; Авезбаев, А.Х. (SCIENCE and SOCIETY, 2020)
The author of the article discusses the features of self-monitoring diaries of young athletes. He also gives recommendation what exercises athletes should do daily.
Keywords: sport; young athlete; check diary; features; physical; functional; medicine; doing exercises